Disease burden of tuberculosis in China from 1990 to 2021 and its prediction to 2036 - Rong Sun; Liang Wang; Hongfang Xia (Frontiers in Public Health)
BackgroundTuberculosis (TB) is one of the oldest infectious diseases and continues to be a major killer of human beings. This paper was designed to provide insights into the disease burden of TB.MethodsThe data was retrieved and downloaded from the latest GBD database. Joinpoint regression was done for the temporal trend analysis. The age-period-cohort model was introduced to get further insights into the independent effects of age, period, and cohort. The BAPC model was utilized to predict ASIR and ASMR from 2022 to 2036.ResultsFrom 1990 to 2021, the ASPR dropped from 31,446 (95% UI: 27,902 to 35,142) to 30,557 (95% UI: 27,693 to 33,531) per 100,000 people, and ASDALYR dropped from 719 (95% UI: 611, 837) to 76 (95% UI: 63, 94) per 100,000 people with an AAPC of −7.009 (95% CI: −7.219, −6.799). ASIR and ASMR decreased from 109 (95% UI: 95, 125) to 36 (95% UI: 33, 40) and from 20 (95% UI: 17, 24) to 2 (95% UI: 2, 3) per 100,000 people, respectively. Men had a higher TB burden than women. The age-period-cohort analysis showed the age effect represented significant fluctuations with a valley at age 5 for incidence rate, and a similar but relatively simple pattern for death rate. Period effect and cohort effect showed both incidence and mortality rates significantly decreased with advancing time points and more recent birth cohorts. At the current decline rate, the ASIR and ASMR would be 26.12 (95%CI: 15.75, 36.48) per 100,000 people and 1.13 (95%CI: 0.45, 1.81) per 100,000 people in 2030, respectively. And the ASIR would be 21.96 (95%CI: 6.14, 37.79) per 100,000 people in 2035.ConclusionTB burden in China has decreased significantly overall in the past years. However, it is still hard to achieve the national goal of “End TB” by 2035, which means more effective strategies for TB prevention and control are urgently needed. Effective strategies aimed at men should include increasing awareness of tuberculosis among both the general population and healthcare workers, promoting smoking cessation and alcohol reduction, enhancing disease screening and treatment access, and providing psychological support and care.